Sobre Iván Olaya Peláez, Pilar González Bernaldo de Quirós, Jorge Márquez Valderrama (eds. académicos), Raza, eugenesia y políticas públicas en América Latina, 1900-1950 - Claudia Agostoni (Historia Mexicana El Colegio de México)
-